The Nordic Model of Work Organization - Gustavsen, Bjørn (Journal of the knowledge economy, 2011)
There are a number of international comparisons of work organization, where the Nordic countries emerge with the most widespread application of such ideas as freedom and learning in work. Two questions arise: first, what are the reasons? Second: what does it mean to apply ideas like freedom and learning in work? The intensive use of specialization as a strategy for productivity occurring during the first part of the previous century led, in the 1950s, to the emergence of initiatives to promote productivity through alternative forms of work organization. “Human relations”, “Quality of working life” and “Lean production” were the main movements to appear out of this turn. The Quality of working life movement, with its demand for a radical redesign of work roles, gained its strongest foothold in the Nordic countries. This article traces the points of origin of this development and provides an overview of the initiatives that have emerged over the years to promote freedom and learning in work. While the notion of “the good work” as work expressing freedom and learning has remained stable, ideas about how to create it have been subject to major changes. While the road to new forms of work organization was originally seen as the implementation of alternative criteria for job design, the ideas dominating today focus on learning, broad participation and a strong link between productivity and innovation. The ability to develop learning-oriented forms of work organization is strongly linked to the constructivist capacity of society.